Análise de impactos econômicos da implantação de parques ciliares: o Parque Ciliar do Ribeirão Onça - Baruc Geremias dos Santos Costa (2022)
Monetary evaluation from ecosystem services, green infrastructure, and sanitation in urban areas, given their often intangible and interdisciplinary nature, remain a major challenge for the scientific community. While World Health Organization (WHO) esteems for each unit invested in sanitation six units in health system are saves, many times social wellness improvements are underestimate or not estimated on decision-making process In order to contribute to reflections on this issue, this work presents a theoretical and methodological framework for the monetary valuation of green areas in urban centers. As a case study, the damage that could be avoided with the implementation of a riparian park in Belo Horizonte/MG, with emphasis on the river environment, was estimated. A hydraulic and hydrological model was calibrated and validated to simulate intense flooding over an urban stream with a drainage area of 214 km². Then, the average annual damage of the floods potentially avoided after the implementation of the riparian park was estimated (eg. HUBERT & LEDOUX, 1999). In relation to water pollution by the release of sewage, the methodology of avoided control costs was applied (eg. MOTTA, 1997; REID, 2005), based on the average cost of local sewage collection and treatment obtained by Pessoa (2019) . Data from the 2010 CENSO were used for the current damage scenario and a hypothetical scenario, assuming intensification of urban occupation, was simulated. All costs and damages are presented based on the date of September 2021. The total damage caused by floods obtained was 4.16% of the average family income, according to social class and the damage caused to the environment in a diffuse way due to the launch of gross sewage in the current scenario was 1.20% of the average family income. Although this analysis carries great uncertainty, the values are of unquestionable relevance for the municipality, which, over 30 years will be equivalent to the average cost of expropriation of families located in their area of implementation, or in 40 years they would be equivalent for the works and expropriations of three other riverside parks implemented in the municipality. It is recommended for future work to seek to integrate different areas of knowledge in order to increase the range of impacts estimated and valued jointly.